2017
DOI: 10.1093/ofid/ofx163.730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum TNF-alpha, IL-6, IL-10, and IFN-gamma Levels in Patients with Crimean–Congo Hemorrhagic Fever

Abstract: Background Crimean–Congo hemorrhagic fever (CCHF) is a potentially fatal disease caused by a tick-borne virus from the Bunyaviridae family. Cytokines plays an important role in the pathogenesis of viral, bacterial, and immunologic diseases. This study aimed to investigate the role of TNF-alpha, IL-6, IL-10, and IFN-gamma levels in the severity of infection and clinical outcome of patients with CCHF. Methods Patients with conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Korva et al, also observed significant differences in IL-10 and GM-CSF between moderate and severe cases (Korva et al, 2019). In another study by Hulva et al, changes in IL-6 and TNF- were noted between moderate and severe cases, but no significant change in IL-8 was observed (Hülya, Yilmaz et al, 2017). Altough IL-6 is often associated with disease severity and fatality, we did not observe any significant difference in IL-6 levels.…”
Section: Discussionsupporting
confidence: 43%
“…Korva et al, also observed significant differences in IL-10 and GM-CSF between moderate and severe cases (Korva et al, 2019). In another study by Hulva et al, changes in IL-6 and TNF- were noted between moderate and severe cases, but no significant change in IL-8 was observed (Hülya, Yilmaz et al, 2017). Altough IL-6 is often associated with disease severity and fatality, we did not observe any significant difference in IL-6 levels.…”
Section: Discussionsupporting
confidence: 43%
“…Korva et al, also observed signi cant differences in IL-10 and GM-CSF between moderate and severe cases 36 . In another study by Hulva et al, changes in IL-6 and TNF-α were noted between moderate and severe cases, but no signi cant change in IL-8 was observed 39 . Although IL-6 is often associated with disease severity and fatality, we did not observe any signi cant difference in IL-6 levels.…”
Section: Discussionmentioning
confidence: 85%